HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN KECENDERUNGAN INSOMNIA PADA LANSIA DI PANTI WREDHA DHARMA BHAKTI SURAKARTA - Utomo, Wahyu; Widodo, Arif (Universitas Muhammadiyah Surakarta, 2009)
Anxiety is a psychological and behavioral response to stress. It’s also important part of human’s experience. Someone may not appear of stress or anxiety, but if we hang out whit them closely there will be stress and anxiety manifestation they experience. Insomnia is difficulnes to start or sleep. This research objective is to analyze the comelation between anxiety level and insomnia tendency on eiderly in dharma bakti Elderly House of surakarta. Method used in this researchis analytic descriptive with cross sectional approach.this research was brought up in dharma bakti Elderly House or surakarta. Sampling method used in this research is simple random sampling whit 47 respondents. Data were collected by means of questioner. And analyzed by means of Chi Square test. The result of this research shows that.(1) Elderly’s anxiety cathegory in Dharma bakti Elderly House is variance from light, medium, and savere (2) Elderly who do ro do not experience insomnia fendency in Dharma Bakti Elderly House of surakarta is relatively the same, and (3) there is a comelation between elderly anxiety level and insomnia fendency in Dharma bakti Elderly House of Surakarta.